AKTUALISASI PENDIDIKAN BELA NEGARA PESERTA DIDIK SD IT GENERASI RABBANI KOTA BENGKULU - Atika Susanti; Panut Setiono; Astri Cornelia Putri; Firda Puspita; Rani Syafitri; Nerliana Aprilianti (JS (JURNAL SEKOLAH), 2021)
Abstract: Actualization of State Defense Education for SD IT Generasi Rabbani Students in Bengkulu City. This study aims to describe the actualization of state defense education SD IT Generasi Rabbani Students, Bengkulu City. The research method used is a case study. Data collection techniques were carried out through interviews and documentation. The actualization of state defense education is carried out through habituation through the implementation of rules, learning Islamic Religious Education and Civic Education, as well as Scouting activities. The teacher's role is carried out based on the role of educators, mentors, and role models. State defense developed in five values: nationalism, the nation and state awareness, loyalty to Pancasila, sacrifice willingness and responsibility.Keywords: Education; State Defence; Civic Education; ScoutAbstrak: Aktualisasi Pendidikan Bela Negara Peserta Didik SD IT Generasi Rabbani Kota Bengkulu. Penelitian ini bertujuan untuk mendeskripsikan aktualisasi pendidikan bela negara peserta didik SD IT Generasi Rabbani Kota Bengkulu. Metode penelitian yang digunakan adalah kualitatif studi kasus. Teknik pengumpulan data dilakukan melalui wawancara dan dokumentasi. Aktualisasi pendidikan bela negara dilaksanakan melalui pembiasaan di lingkungan sekolah melalui pelaksanaan tata tertib, pembelajaran Pendidikan Agama Islam dan Pendidikan Kewarganegaraan, serta kegiatan Pramuka. Peran guru dalam aktualisasi pendidikan bela negara dilakukan berdasarkan peran sebagai pendidik, pembimbing, dan model atau teladan. Pendidikan bela negara yang dikembangkan dalam lima nilai: cinta tanah air, sikap sadar akan bangsa dan negara, setia kepada Pancasila, rela berkorban dan tanggung jawab. Kata kunci: Pendidikan; Bela Negara; Pendidikan Kewarganegaran, Pramuka